LDL-C Concentrations and the 12-SNP LDL-C Score for Polygenic Hypercholesterolaemia in Self-Reported South Asian, Black and Caribbean Participants of the UK Biobank - Gratton, Jasmine; Finan, Chris; Hingorani, Aroon D.; Humphries, Steve E.; Futema, Marta (Frontiers in Genetics, 2022)
Background: Monogenic familial hypercholesterolemia (FH) is an autosomal dominant disorder characterised by elevated low-density lipoprotein cholesterol (LDL-C) concentrations due to monogenic mutations in LDLR, APOB, PCSK9, and APOE. Some mutation-negative patients have a polygenic cause for elevated LDL-C due to a burden of common LDL-C-raising alleles, as demonstrated in people of White British (WB) ancestry using a 12-single nucleotide polymorphism (SNP) score. This score has yet to be evaluated in people of South Asian (SA), and Black and Caribbean (BC) ethnicities. Objectives: (1) Compare the LDL-C and 12-SNP score distributions across the three major ethnic groups in the UK: WB, SA, and BC individuals; (2) compare the association of the 12-SNP score with LDL-C in these groups; (3) evaluate ethnicity-specific and WB 12-SNP score decile cut-off values, applied to SA and BC ethnicities, in predicting LDL-C concentrations and hypercholesterolaemia (LDL-C>4.9mmol/L). Methods: The UK Biobank cohort was used to analyse the LDL-C (adjusted for statin use) and 12-SNP score distributions in self-reported WB (n=353,166), SA (n=7,016), and BC (n=7,082) participants. To evaluate WB and ethnicity-specific 12-SNP score deciles, the total dataset was split 50:50 into a training and testing dataset. Regression analyses (logistic and linear) were used to analyse hypercholesterolaemia (LDL-C>4.9 mmol/L) and LDL-C. Findings: The mean(+SD) measured LDL-C differed significantly between the ethnic groups and was highest in WB (3.73(+0.85)mmol/L), followed by SA (3.57(+0.86)mmol/L, p<2.2x10-16), and BC (3.42(+0.90)mmol/L) participants (p<2.2x10-16). There were significant differences in the mean(+SD) 12-SNP score between WB (0.90(+0.23)) and BC (0.72(+0.25), p<2.2x10-16), and WB and SA participants (0.86(+0.19), p<2.2x10-16). In all three ethnic groups the 12-SNP score was associated with measured LDL-C (R2(95%CI): WB=0.067(0.065-0.069), BC=0.080(0.063-0.097), SA=0.027(0.016-0.038)). The odds ratio and the area under the curve for hypercholesterolaemia were not statistically different when applying ethnicity-specific or WB deciles in all ethnic groups. Interpretation: We provide information on the differences in LDL-C and the 12-SNP score distributions in self-reported WB, SA, and BC individuals of the UK Biobank. We report the association between the 12-SNP score and LDL-C in these ethnic groups. We evaluate the performance of ethnicity-specific and WB 12-SNP score deciles in predicting LDL-C and hypercholesterolaemia.